Politici sociale de locuire - Briciu, Cosmin (Calitatea Vieții, 2016)
The article argues, within an European comparative framework of the analysis regarding the housing problems in Romania and the answer provided by policies for a series of developments considered as highly desirable: (i) housing policies would have to encompass a larger spectrum of programmes and tools than currently functional, in order to address both large parts of the population faced with bottlenecks in accesing good quality housing and the vulnerable and socially excluded population, (ii) a housing strategy would have to be designed in order to coherently plan these newly proposed housing programmes and tools, (iii) radical reform is needed for the social housing programme, which needs much more generous financing and should assume a wider coverage of the population, (iv) the public administration system would have to take ownership of the responsibility for the policies tackling the problems of the homelessness: launch a series of programmes for the prevention of house losses and for the social reintegration of the homeless. In order to highlight the importance of such developments, the article discusses the main problems in the area of housing and existing intervention capacity.